(Men)tal health: Perceptions of depression in men and women - Nina Freiberger; Teresa Lynch; Glenna L. Read; Alexandra M. Blouin (SSM - Mental Health, 2023)
Despite evidence indicating that depression is prevalent in men, gender stereotypes persist that position the disorder as feminine. This misperception may contribute to men's underdiagnosis with and undertreatment for depression. We applied the shifting standards model (SSM) to advance predictions about gender differences in the evaluation of individuals described as experiencing depression. These predictions took the form of objective and subjective evaluations, as well as minimum and confirmatory standards. We randomly assigned participants (N = 430) in a 3 (target gender: man, woman, control) x 2 (judgment standards: minimum, confirmatory) between-subjects experiment. Participants read a vignette describing a woman, man, or individual of unspecified gender and provided the evidence they would need to suspect or confirm depression in the target individual consistent with minimum and confirmatory judgment standards. Results from the pilot and main studies indicate more gender similarities than differences. We discuss the findings with respect to the SSM and how the increase in mental health salience during the COVID-19 pandemic may have mitigated gender stereotypical views of depression.